Responses of sub-ice platelet layer thickening rate and frazil-ice concentration to variations in ice-shelf water supercooling in McMurdo Sound, Antarctica - Cheng, Chen; Jenkins, Adrian; Holland, Paul R.; Wang, Zhaomin; Liu, Chengyan; Xia, Ruibin (The Cryosphere, 2019)
Persistent outflow of supercooled ice-shelf water (ISW) from beneath McMurdo Ice Shelf creates a rapidly growing sub-ice platelet layer (SIPL) with a unique crystallographic structure under the sea ice in McMurdo Sound, Antarctica. A vertically modified frazil-ice-laden ISW plume model that encapsulates the combined non-linear effects of the vertical distributions of supercooling and frazil concentration on frazil-ice growth is applied to McMurdo Sound and is shown to reproduce the observed ISW supercooling and SIPL distributions. Using this model, the dependence of the SIPL thickening rate and depth-averaged frazil-ice concentration on ISW supercooling in McMurdo Sound is investigated and found to be predominantly controlled by the vertical distribution of frazil concentration. The complex dependence on frazil concentration highlights the need to improve frazil-ice observations within the sea-ice–ocean boundary layer in McMurdo Sound.